Domiciliary nebulised salbutamol solution in severe chronic airway obstruction. - Wilson, R S (1980)
Nine patients with severe chronic airway obstruction secondary to chronic bronchitis and emphysema all preferred nebulised salbutamol solution to placebo in a double-blind controlled trial. Four of the patients who had previously received domiciliary nebulised salbutamol failed to complete the placebo period, though all completed the active period. Five others improved subjectively on active therapy, and showed a significant improvement in morning and evening peak flows. Symptom scores for breathlessness, wheezing, and sputum production were lower in the active treatment period and standard aerosol usage fell, although these changes might have been due to chance. Patients with severe chronic airway obstruction who do not respond to conventional bronchodilator therapy should be considered for this form of treatment.